MEDIA EFEKTIVITAS MEDIA INTERAKTIF BERBASIS ADOBE FLASH UNTUK MENINGKATKAN BERPIKIR KRITIS PADA MATERI EKOSISTEM MANGROVE - Apriani, Ade; Yustina, Yustina; Zulfarina , Zulfarina (Bio-Lectura : Jurnal Pendidikan Biologi, 2024)
The purpose of this research is to develop valid interactive media based on Adobe Flash. This type of research is research and development, the ADDIE development model is based on five stages, ie. analysis, planning, development, implementation, evaluation, in this study up to the fifth stage, i.e. evaluation Therefore, an interactive media based on Adobe Flash was developed to improve students' critical thinking. This study was conducted at Riau University. Students of the biology education study program of the Department of Mathematics and Science Education (PMIPA) of the Faculty of Teacher Education and Educational Sciences (FKIP) of Riau University, a total of 2 classes, participated in this study. This study uses a quasi-experimental research design where the students studied are environmental science and disaster mitigation courses. The sample was determined by saturated sampling, the test and control groups were determined by random sampling using the lottery method. Adobe Flash-based interactive media was taught in the experimental class, and Adobe Flash-based interactive media was not taught in the comparison class. In practice, students are given a pre- and post-test. The research parameter is students' ability to think critically. According to Angelo 1995, critical thinking skills are used as indicators of critical thinking skills with five indicators which are analysis, synthesis, identification, problem solving, conclusion and evaluation. Data collection on critical thinking is done through pre-test and post-test questions. The data will be presented and analyzed definitively. Students' critical thinking scores improved with an n-growth index of 0.38 (middle class). In general, interactive media based on Adobe Flash can improve students' critical thinking.